DDRE-21. LOMUSTINE AND TARGETED-CYTOKINE THERAPY: A BENEFICIAL LIAISON FOR RECURRENT GLIOBLASTOMA. (12th November 2021) - Weiss, Tobias; Look, Thomas; Puca, Emanuele; De Luca, Roberto; Hemmerle, Teresa; Roth, Patrick; Neri, Dario; Weller, Michael
Abstract: Treatment options for recurrent glioblastoma are limited and except from regorafenib (potentially), no other agent has demonstrated superior activity to lomustine. Therefore, there is an urgent need for more effective treatment strategies for recurrent glioblastoma. We investigated the combination of lomustine or bevacizumab that are frequently used for recurrent glioblastoma with L19TNF (onfekafusp alfa), a systemically administered tumor-stroma targeting antibody-cytokine fusion protein that enables a targeted delivery of tumor-necrosis factor (TNF)a to the tumor. In immunocompetent orthotopic glioma mouse models, the combination of lomustine and L19TNF demonstrated the strongest anti-tumor activity, acted in synergy and cured a majority of tumor-bearing mice, whereas lomustine or L19TNF monotherapy only had only very limited anti-tumor activity. Ex vivo profiling of the tumors and tumor-infiltrating immune cells from immunocompetent or immunodeficient hosts demonstrated immune-dependent cytotoxic and cytostatic effects on the glioma cells, and a strong increase of tumor-infiltrating immune cells upon combination therapy in immunocompetent models. Based on these encouraging results, we translate this combinatorial therapy to patients with recurrent glioblastoma. For the first patients, the treatment with lomustine and L19TNF was well tolerated and led to stable disease with a reduction in tumor perfusion. More patients are recruited in an ongoing phase I/II clinical trial with lomustine and L19TNF for patients with recurrent glioblastoma (NCT04573192).